Determinants of poverty rate in Java Island: Poverty alleviation policy - Imade Yoga Prasada; Tri Fatma Mala Yulhar; Tia Alfina Rosa (Jurnal Ekonomi Pembangunan, 2020)
Poverty is currently a major problem that must be resolved in various regions in Indonesia, including areas in Java. Java Island is the island with the highest number of poor people compared to other islands in Indonesia. The aim of this study was to determine the determinants of poverty levels in Java and formulate policy recommendations that can be implied to overcome poverty. Research variables have used secondary data from six provinces in Java sourced from the Central Statistics Agency, namely poverty level data, Human Development Index (HDI), inflation rate data, open unemployment rate data, and Regional Minimum Wage data (UMR). The data was compiled into panel data and analyzed using OLS Model. The analysis showed that the determinants of poverty levels in Java were inflation rates, Human Development Index, Regional Minimum Wages, and open unemployment rates, so that all determinants need to be considered properly to formulate policy recommendations that able to overcome poverty in Java.